Chimerical pyrene-based [7]helicenes as twisted polycondensed aromatics - Buchta, Michal; Rybáček, Jiří; Jančařík, Andrej; Kudale, Amit A; Buděšínský, Miloš; Chocholoušová, Jana Vacek; Vacek, Jaroslav; Bednárová, Lucie; Císařová, Ivana; Bodwell, Graham J; Starý, Ivo; Stará, Irena G (Chemistry (Weinheim an der Bergstrasse, Germany), 2015)
Chimerical pyrene-based dibenzo[7]helicene rac-1 and 2H-pyran[7]helicene (M,R,R)-(-)-2, in which two pyrene subunits are fused to the [7]helicene/[7]heterohelicene scaffold, were synthesised by means of Ni(0) - or Co(I) -mediated [2+2+2] cycloisomerisation of dipyrenyl-acetylene-derived triynes. Pyrene-based dibenzo[7]helicene 1 was obtained in enantioenriched form by enantioselective cycloisomerisation under Ni(0) /QUINAP catalysis (57 % ee) or in enantiopure form by racemate resolution by liquid chromatography on a chiral column. 1,3-Allylic-type strain-controlled diastereoselective cycloisomerisation was employed in the synthesis of enantiopure (M,R,R)-(-)-2. Physicochemical properties of 1 and 2 encompassing the helicity assignment, stability to racemisation, X-ray crystal structure, UV/Vis, experimental/calculated electronic circular dichroism and fluorescence spectra were studied. Accordingly, comparison of the X-ray crystal structure of (M,R,R)-(-)-2 with calculated structures (DFT: B3LYP/cc-pVDZ, B97D/cc-pVDZ) indicated that its helical backbone is slightly over-flattened owing to intramolecular dispersion forces between tert-butylated pyrene subunits. Both 1 and 2 are fluorescent (with quantum yields in dichloromethane of ΦF =0.10 and 0.17, respectively) and are suggested to form intramolecular excimer states upon excitation, which are remarkably stabilised and exhibit large Stokes shifts (296 and 203 nm, respectively).
Keywords: chirality; alkynes; cycloisomerisation; asymmetric synthesis; helical structures